Scoping review of literature and systematic search of web-based resources: parasport classification instructions, experiences, and outcomes - Lawson, J. A.; Latimer-Cheung, A. E. (International Review of Sport and Exercise Psychology, 2024)
While classification is essential to parasport, members of the Paralympic Movement commonly report having limited access to information on the topic. Despite increased academic interest in recent years, the total body of research on classification has not yet been mapped or documented. To assess the breadth of literature on classification, we conducted a scoping review following the protocol set forth by Arksey and O`Malley (2005). Additionally, we completed a six-step systematic online search as outlined by Stansfield et al. (2016) to document the type and quality of information on classification available outside bibliographic databases. The most frequent topics discussed in the literature were (a) coach/classifier roles during classification, (b) athletes` perspectives on classification, and (c) the influence of classification on athletes` participation (e.g. on social dynamics, athlete development). Webpages reviewed were of relatively low quality, with <50% reporting authorship, references, or a statement of disclosure. Webpages reviewed were primarily produced by national/international sport organizations and provided more professional (i.e. technical) information on classification than inter-/intrapersonal information or instruction. This review provides insight into the type and quality of classification knowledge available to parasport participants and may inform future research and practice related to parasport at all levels.